2021
DOI: 10.1002/agt2.36
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting an ancient inorganic aggregation‐induced emission system: An enlightenment to clusteroluminescence

Abstract: Organic and inorganic clusteroluminescence have attracted great attention while the underlying mechanisms is still not well understood. Here, we employed a series of ancient inorganic complexes platinocyanides with aggregation‐induced emission property to elucidate the mechanism of clusteroluminescence including how does the chromophore form and how does the solid structures influence the luminescence behaviors. The results indicate that the isolated platinocyanide cannot work as a chromophore to emit visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…[6,7] AIE phenomenon can be observed both in organic and inorganic system. [8,9] Prototypical AIEgens such as tetraphenylethene (TPE) and pentaphenylsilole have been extensively studied and their unique properties also trigger the photophysical study in the aggregate state. [10,11] Through modulate the state of aggregate, AIEgens with desired photophysical properties could be used for practical applications.…”
Section: Insights Into Optical Probes Based On Aggregation-induced Emission: From Restriction Of Intramolecular Motions To Dark Statementioning
confidence: 99%
“…[6,7] AIE phenomenon can be observed both in organic and inorganic system. [8,9] Prototypical AIEgens such as tetraphenylethene (TPE) and pentaphenylsilole have been extensively studied and their unique properties also trigger the photophysical study in the aggregate state. [10,11] Through modulate the state of aggregate, AIEgens with desired photophysical properties could be used for practical applications.…”
Section: Insights Into Optical Probes Based On Aggregation-induced Emission: From Restriction Of Intramolecular Motions To Dark Statementioning
confidence: 99%
“…This unconventional photophysical process is termed as clusterization-triggered emission and the corresponding emission is known as clusteroluminescence. [22][23][24][25] The previous studies suggested that strong intermolecular interactions among the closely packed molecules generated new emissive species and stabilized excited excitons to produce clusteroluminescence. [26][27][28] Apart from intermolecular interaction, intramolecular through-space conjugation (TSC) was also proved to play an important role in clusteroluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic delocalization and coupling between electron-rich groups (e.g., carbonyl, hydroxyl, and sulfhydryl groups) can generate new emissive species and stabilize excitons to produce such clusteroluminescence. 58,87 These new species usually produce emission with a longer wavelength than the intrinsic shortwavelength emission of the electron-rich groups from throughbond conjugation.…”
Section: Clusteroluminescencementioning
confidence: 99%